1996
DOI: 10.1017/s0022215100135728
|View full text |Cite
|
Sign up to set email alerts
|

An audit of the cochlear implant service in Manchester

Abstract: The adult cochlear implant programme in Manchester was established in 1988 and the evaluation of the cochlear implant service involved the first 58 implants users (mean age = 51.65 years, range 19–75 years). Questionnaires were sent to implant users and their partners to evaluate the service with regard to provision of information, clinical care during in-patient assessments, waiting times, operation for cochlear implant and postoperative rehabilitation. The results show that the majority of patients (78 per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The possibility to meet other CI-users was one of the most important factors related to pre-operative information reported by both the CI-users and their significant others in the present study. This is also in line with the results of an audit conducted by the Manchester CI Programme as early as in the mid-1990s [21], and is similar to the clinical practice adopted by CI-teams worldwide. Moreover, both the CI-users and their significant others in our study emphasized specifically the importance of information related to the time it takes before the CI-user has learned to hear with the implant.…”
Section: Discussionsupporting
confidence: 87%
“…The possibility to meet other CI-users was one of the most important factors related to pre-operative information reported by both the CI-users and their significant others in the present study. This is also in line with the results of an audit conducted by the Manchester CI Programme as early as in the mid-1990s [21], and is similar to the clinical practice adopted by CI-teams worldwide. Moreover, both the CI-users and their significant others in our study emphasized specifically the importance of information related to the time it takes before the CI-user has learned to hear with the implant.…”
Section: Discussionsupporting
confidence: 87%
“…CI is at present the only treatment option for deafened patients with a documented effect (5). One recent study showed that the majority of patients (78%) felt that the implant offered as much or more benefit than expected (6). Another study documented a steady increase in personal income for the group that underwent implantation (2).…”
Section: Statisticsmentioning
confidence: 99%
“…Expectations about the implant procedure, its potential outcomes, and the considerable post-implant rehabilitation required must be clear and realistic. The implant team needs to provide a service that meets the needs of its patients (Mawman et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Expectations about the implant procedure, its potential outcomes, and the considerable post-implant rehabilitation required must be clear and realistic. The implant team needs to provide a service that meets the needs of its patients (Mawman et al, 1996).From the very beginning of CI it was quite clear that the post-operative rehabilitation consists out of two phases: first the acute part soon after surgery to adjust the implantee to his/her new device and to fit the device to his/her individual need, and second the long-term part to ensure the functioning of the device for lifelong use, here referred to as 'aftercare'.As advances in CI technology expand, the need/ demand for CI services continues to grow. Therefore, a major question for every CI program is how can access to CI services be assured for the increasing number of CI recipients without degrading the basic quality of their individual long-term care?…”
mentioning
confidence: 99%